Separation of sphalerite and dolomite using sodium alginate as an environmentally friendly depressant in a carbonate-hosted Pb-Zn ore system. (20th December 2022) - Wang, Changtao; Liu, Runqing; Xie, Feifei; Zhai, Qilin; Sun, Wei; Wen, Xiaofei; Li, Jie
Abstract: Magnesium in zinc concentrate causes serious environment problems during hydrometallurgical processes. In the flotation of carbonate-hosted Pb-Zn ore, the separation of dolomite is critical to obtain high-quality zinc concentrate. In this study, fine-grained dolomite was found to be more floatable than coarse-grained dolomite, and it was the main cause of magnesium contamination. Entrainment dominated the flotation of fine-grained dolomite. The environmentally friendly sodium alginate (SA) was successfully used to depress dolomite, and the adsorption mechanism was found to be SA molecules chelating with Ca sites on the surface of the dolomite. The adsorption of SA enhanced dolomite hydrophilicity and increased the particle size due to flocculation, which reduced the entrainment. SA depressed sphalerite during flotation, but the Cu 2+ ions enhanced butyl xanthate (BX) adhesion and inhibited the depressive effect of SA. Thus, sphalerite maintained good floatability. Overall, dolomite was selectively depressed by SA during the flotation of sphalerite, and the content of magnesium in the zinc concentrate decreased significantly from 3.65% to 2.37%. This study used SA as a dolomite depressant and obtained a higher quality zinc concentrate when floating a carbonate-hosted Pb-Zn ore, indicating its potential for commercialization and widespread industrial application. Graphical abstract: Image 1 Highlights: Fine-grained dolomite easily entered foams and causing magnesium-pollution in Zn concentrate. SA depressed dolomite and sphalerite flotation in the absence of Cu 2+ . The anchored copper ions on sphalerite surface enhanced BX adsorption and shield the depressive effect of SA. Dolomite was strongly depressed by SA and maintained un-floatable in the system of Cu 2+ and BX. The flotation separation of sphalerite and fine-grained dolomite was achieved by SA in the presence of Cu 2+ .